2009
DOI: 10.1111/j.1478-3231.2009.02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan attenuates progression of steatohepatitis in mice: role of hepatic macrophage infiltration and effects on adipose tissue

Abstract: In this study, we revealed that Tel attenuated steatohepatitis progression by suppressing the macrophage infiltration into the liver. Tel also affected the reduction of adipocyte size and elevation of serum adiponectin. Tel might serve as a new therapeutic strategy for NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 38 publications
(31 reference statements)
5
46
1
1
Order By: Relevance
“…With the association of obesity and NAFLD in the metabolic syndrome, it is not surprising that increased serum and liver TNF-α expression is observed in patients 39 and rodent models of NAFLD. 40,41 Several data suggested the involvement of TNF-α and IL-6 in the metabolic syndrome and progression of NAFLD, perhaps, in part through increased mitochondrial dysfunction and 42,43 TNF-α also can contribute to the development of insulin resistance through disruption of the insulin signaling cascade at the level of insulin receptor substrate-1 pathway by Ang II. 44 Ang II-infused rats presented increased IL-6 expression in the liver with associated increase in monocyte recruitment and overall inflammation.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…With the association of obesity and NAFLD in the metabolic syndrome, it is not surprising that increased serum and liver TNF-α expression is observed in patients 39 and rodent models of NAFLD. 40,41 Several data suggested the involvement of TNF-α and IL-6 in the metabolic syndrome and progression of NAFLD, perhaps, in part through increased mitochondrial dysfunction and 42,43 TNF-α also can contribute to the development of insulin resistance through disruption of the insulin signaling cascade at the level of insulin receptor substrate-1 pathway by Ang II. 44 Ang II-infused rats presented increased IL-6 expression in the liver with associated increase in monocyte recruitment and overall inflammation.…”
Section: -13mentioning
confidence: 99%
“…With the association of obesity and NAFLD in the metabolic syndrome, it is not surprising that increased serum and liver TNF-α expression is observed in patients 39 and rodent models of NAFLD. 40,41 Several data suggested the involvement of TNF-α and IL-6 in the metabolic syndrome and progression of NAFLD, perhaps, in part through increased mitochondrial dysfunction and 44 Ang II-infused rats presented increased IL-6 expression in the liver with associated increase in monocyte recruitment and overall inflammation. 45 A recent study showed that Ang-(1-7) was able to reduce inflammatory markers in rats with diabetic nephropathy.…”
mentioning
confidence: 99%
“…In recent years, TEL has been reported to participate in protecting against NAFLD by regulating the expression of a variety of factors (8)(9)(10)(11). Leptin is an independence flag that could mark the progression and severity of NAFLD, and is closely related to liver lipid metabolism, steatosis, inflammation and fibrosis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In effect, rodents with genetic deficiency of RAS components involved in angiotensin II production or intracellular signaling show reduced body fat and improvement of those metabolic parameters commonly linked with obesity (Massiéra et al 2001, Kouyama et al 2005, Yvan-Charvet et al 2009). Furthermore, inhibition of the RAS by prolonged administration of angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers, or a renin inhibitor to several murine models of obesity and diabetes also produces adipose tissue mass reduction, restitution of the normal adipokine profile, and recovery of glucose and lipid metabolism indicators (Mathai et al 2008, Kudo et al 2009, Santos et al 2009, Stucchi et al 2009, Weisinger et al 2009). These features associate with increased abundance of small functional adipocytes in visceral adipose tissue (Furuhashi et al 2004, Lee et al 2008 and expression of molecular markers of adipogenesis (Tomono et al 2008) in treated animals.…”
Section: Introductionmentioning
confidence: 99%